Commutativity of MA-Semirings with Involution through Generalized Derivations. (14th December 2020) - Ali, Liaqat; Aslam, Muhammad; Qureshi, Muhammad Imran; Khan, Yaqoub Ahmed; Rehman, Shafiq Ur; Farid, Ghulam
Abstract : In this paper, we study the generalized derivations of MA-semirings with involution. We discuss some differential identities satisfied by the generalized derivations which force the semirings with involution to be commutative.